A stereo photogrammetry scanning methodology, for precise and accurate 3D digitization of small parts with sub-millimeter sized features. Issue 1 (2015) - Galantucci, L.M.; Pesce, M.; Lavecchia, F.
Abstract: This paper presents a scanning methodology based on close-range stereo photogrammetry, suitable for precise and accurate 3D digitization of objects of few millimeters in length and features in sub-millimeter scale. The authors propose an efficient alternative to other scanning methodologies currently used for such applications, as the conoscopic holography, with the aim to reduce the scanning time and obtain a result which also contains information related to the real texture of the object. An experimental plan has been designed and implemented in order to investigate the accuracy and precision of the 3D scans.